Analysis of corporate cash holdings of firms in Malaysia. Issue 2 (29th April 2014) - Wasiuzzaman, Shaista
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to understand the motives behind the levels of cash holdings and the theory that may be able to explain why these firms hold so much cash. Design/methodology/approach – Annual financial data and stock prices of 192 firms from six different sectors on the Bursa Malaysia are collected for the period 2000-2007. Analysis using the non-parametric Kruskal–Wallis test is carried out to analyze industrial and time differences in cash holdings. The ordinary least square (OLS) regression technique is used to understand the relationships between various attributes with the level of cash holdings. Due to issues of endogeneity, the generalized method of moments method is also applied. Findings – Significant differences are found to exist in the level of cash holdings between firms and across time. It is found that firms adjust to a target level of cash holdings, although this is done relatively slowly. Also, significance of firm characteristics and their relationships with cash holdings indicate that other than the pecking order theory, the trade-off theory and the agency theory can help explain the level of cash holdings of firms in Malaysia. Originality/value – Most studies on cash holdings have been carried out in developed countries. Malaysia is an advanced emerging market with significant state control and firm structure being largely family-oriented. Hence, a study on a different market with different types of firm structures will contribute significantly to the existing literature on corporate cash holdings.